Social support in schools and related outcomes for LGBTQ youth: a scoping review - Enoch Leung; Gabriela Kassel-Gomez; Samantha Sullivan; Flavio Murahara; Tara Flanagan (Springer, 2022)
Abstract Recent research has increasingly focused on positive factors and supports for LGBTQ youth. This scoping review explores existing social support for LGBTQ youth in schools through the Ecological Systems Theory to respond to the following four objectives: (1) define social support systems in schools, (2) identify current research on outcomes for LGBTQ youth, (3) identify barriers to support LGBTQ youth in schools, and (4) identify areas for future research for LGBTQ youth and social support in schools. A systematic search (Arksey and O'Malley in Int J Soc Res Methodol 8(1):19-32, 2005) between 2007 through 2021 resulted in 94 articles. This review gave rise to an organizational framework to consolidate various systems of social support for LGBTQ youth in schools. Social support consisted of seven social support systems (family, curriculum, family, peers, school policies, GSAs and programs, and school climate) that are positively associated with the promotion of positive socioemotional, behavioural, and educational outcomes for LGBTQ youth. Though the literature has been clear surrounding the risks associated with LGBTQ youth, this scoping review provides a positive outlook on LGBTQ youth's school experiences and how these systems of social support allow for LGBTQ youth to act as active participants to foster a positive school climate and sense of safety.